Acetylcholinesterase in the fast extraocular muscle of the mouse by light and electron microscope autoradiography (The Rockefeller University Press, 1978)
The distribution of acetylcholinesterase (ACHe) in the twitch fibers of the extraocular muscles of the mouse was examined by light and electron microscope autoradiography after labeling with radioactive diisopropyl fluorophosphate (DFP) with, and without, 2-pyridine aldoxime methiodide (2-PAM) reactivation. The values obtained were compared with those previously reported for the diaphragm and sternomastoid muscles. The extraocular muscles were studied because they differ from the other two muscles in that they are among the fastest of the mammalian muscles, yet their endplates have sparse junctional folds. They could thus provide information on the extent to which ACHe concentration is an invariant feature of endplate morphology and what, if any aspects may be related to their fast speed of response. We found, using light microscope autoradiography, that in the twitch fibers of the extraocular muscle, there is n average of 6.4 +/- 2.1 X 10(7) DFP- binding sites per endplate, of which 29% (1.8 X 10(7)) are reactivated by 2-PAM and are thus AChe. The morphology of the extraocular endplates allowed us to conclude, on statistical grounds, that the AChe site are probably localized not only along the surface area of the postjunctional membrane (PJM) but also along the surface of the presynaptic axonal membrane. Based on this localization, we calculate 7,800 DFP sites and 2,500 2-PAM-reactivated sites/micron 2 of surface area of pre-and postjunctional membrane. This stacking density of DFP- binding sites per surface area of membrane ( probably in the overlying sheets of basal lamina) is very similar to that in the diaphragm and sternomastoid muscles.